Modificação e caracterização da superfície do aço inoxidável Martensítico AISI 410 - Bincoleto, Alexandre Vinicius Leite (Universidade Federal de São Carlos, 2010)
This work deals about the surface modification of the AISI 410 martensitic stainless steel. The modification of steel surfaces is important for the improvement of its mechanical and tribological properties. Among the modification processes, there are coating, deposition of thin films, and ion implantation. The AISI 410 stainless steel is widely applied by manufacturers of steam turbine for the production of blades, rods, and valves, which are the components that suffer more the abrasion by water vapor. This work compares the main surface modifications employed in the AISI 410 stainless steel in order to define which the best deposition processes are regarding their final application (nitriding, carbonitriding, and boronizing). The structures, the morphologies, and the chemical compositions of the modified surfaces had been characterized by XRD. Also optical microscopy was used for the analysis of the microstructural modifications and measurement of the surface hardness.
Surface modification and characterization of the AISI 410 Martensitic stainless steel
Keywords: Aço inoxidável; Nitretação; Modificação superficial; Tratamento superficial; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA